Oesophageal lichen planus: the efficacy of topical steroid‐based therapies. Issue 2 (17th November 2016) - Podboy, A.; Sunjaya, D.; Smyrk, T. C.; Murray, J. A.; Binder, M.; Katzka, D. A.; Alexander, J. A.; Halland, M.
Summary: Background: Oesophageal lichen planus is an idiopathic inflammatory disorder characterized by significant oesophageal stricturing. Oesophageal lichen planus is a rare, difficult to diagnose, and likely an under recognized disease. As a result, there is no standardized approach to therapy and treatment strategies vary. Aim: To examine the utility of topical steroid therapy (fluticasone or budesonide) in the management of oesophageal lichen planus. Methods: A retrospective chart review was conducted of patients diagnosed with oesophageal lichen planus who underwent baseline and follow up endoscopy pre and post topical steroid therapy between 1995 and 2016 at Mayo Clinic, Rochester MN. Average time between upper GI endoscopy was 3.2 months (0.7–11.7). Swallowed steroid preparations included fluticasone 880 μg twice daily or budesonide 3 mg twice daily. Patients were reviewed for symptomatic response to therapy using the Dakkak‐Bennett dysphagia score (0–4, no dysphagia to total aphagia). Pre‐ and post‐endoscopic findings were assessed. Additional baseline demographic, endoscopic, and histologic data were also obtained. Results: We identified 40 patients who met the inclusion criteria. A significant reduction in median dysphagia score from 1 (0–4) to 0 (0–3) after steroid therapy ( P < 0.001) was noted. 62% of patients reported resolution of their dysphagia after receiving topical corticosteroids. 72.5% had an endoscopic response to steroid therapy. Conclusion: Topical swallowed budesonide or fluticasone appear to effective treatment for oesophageal lichen planus.